Students’ Perception of The Implementation of AI Technology: Gemini To Enhance Writing Skills - Antony, Rian; Hendrikus Erda Putra (Institut of Shanti Bhuana, 2025)
Writing is a fundamental skill for EFL students. This study explores students’ perceptions of using Gemini, an AI technology developed by Google, to enhance writing skills. Two questions guided the research: (1) What are students’ perceptions of Gemini in improving writing skills? and (2) How does Gemini contribute to students’ writing improvement? A descriptive mixed-method design was applied with 36 Grade IX students of Mater Dei Junior High School. Data were obtained through questionnaires, writing assessments, and interviews. The results indicated that students had positive perceptions of Gemini, and their writing scores improved after its use. Interview findings also confirmed that Gemini provided valuable assistance, personalized feedback, and supported time management. This research contributes to the growing body of knowledge on AI integration in language learning, particularly by highlighting the potential of Gemini as a practical tool to support EFL writing instruction and personalized learning.